Mechanisms of biocontrol against strawberry angular leaf spot disease by a constructed Paenibacillus polymyxa MY-J3 microbial consortium - Ma, Mengxiang; He, Haowen; Li, Yimei; Deng, Chunju; Zhang, Jinhao; Lv, Rong; Li, Hongmei; Li, Hao; Ou, Kunyu; Ji, Guanghai (Frontiers in Agronomy, 2026)
Angular leaf spot (ALS) disease, caused by Xanthomonas fragariae, has emerged as a devastating bacterial pathogen, posing a serious threat to strawberry production. This study aimed to construct an effective synthetic microbial consortium using antagonistic bacteria and to elucidate its biocontrol mechanisms against ALS through an integrated approach including culturomics, real-time quantitative PCR (qPCR), and high-throughput sequencing of the phyllosphere microbiome. The main findings are as follows: Three synthetic microbial consortia were assembled following compatibility assessment. Among these, the combination of Paenibacillus polymyxa MY-J3 and Lysobacter antibioticus HY (designated M+H) demonstrated superior efficacy, achieving a relative control efficacy of 76.15% and 74.26% under greenhouse and field conditions, respectively. Using a tailored qPCR assay for X. fragariae detection, the M+H treatment reduced pathogen abundance by 99.99% compared to the control. The consortium M+H markedly up-regulated the expression of host defense-related genes while down-regulating key virulence genes of X. fragariae. The crude extract from the M+H consortium exhibited a minimum inhibitory concentration (MIC) of 80 mg/mL against X. fragariae and significantly disrupted bacterial biofilm formation, cell surface hydrophobicity, extracellular polysaccharide production, and reduced pathogenicity. Furthermore, treatment with the consortium notably altered the diversity and composition of the strawberry phyllosphere bacterial community. The microbial consortium M+H can suppress the occurrence of the ALS through multiple mechanisms, demonstrating promising application prospects.